ANALISIS MINAT MAHASISWA FIP UNM DALAM MENGIKUTI MAGANG STUDI INDEPENDEN BERSERTIFIKAT PADA PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA - Andi Ashabul Qaffih; Muh Ardiansyah; Irmawati, Irmawati (Yayasan Nusantara Hasana Berdikari, 2025)
This study aims to analyze the interest of students of the Faculty of Education (FIP) of Makassar State University in participating in the Certified Independent Study Internship Program (MSIB), part of the Merdeka Belajar Kampus Merdeka (MBKM) policy. A quantitative approach with a descriptive survey type was used. The research sample was 95 students from four study programs at FIP ​​UNM, taken using stratified random sampling and the Slovin formula. Data collection through questionnaires, observations, and documentation. The research instrument was proven valid through the Pearson Product Moment correlation, and reliable with a Cronbach's Alpha value of 0.842. The results showed that students' interest in MSIB was complex. Although there was a high initiative in seeking information and considering MSIB in the study plan, positive perceptions were not always in line with students' specific motivation or readiness. on average, they did not feel the suitability of the program to their field of study, and were not motivated to gain work experience or new experiences through MSIB, even the experiences offered were considered less attractive to almost half of the students. Supporting factors for interest include active initiative in accessing information and the desire to integrate MSIB into study planning. However, significant barriers were identified: unpreparedness for full-time commitment, reluctance to be placed outside the city/campus and relatively very low commitment to completing the program, as well as not being ready to face challenges and the need to improve socialization. The conclusion confirms that although MSIB is a strategic opportunity, optimal participation is hampered by the misalignment of intrinsic motivation, time and location commitment, and mental readiness. Recommendations include adjusting the communication of benefits, increasing program flexibility, and providing more intensive readiness support.